Developing Educators' Mastery of Religious Materials to Increase the Competitiveness of Islamic Boarding Schools - Parino, Parino; Chotib, Moch.; Muhith, Abd.; Yusuf, Thorieq Moh. (Eduprof : Islamic Education Journal, 2025)
Developing the quality of educators in Islamic boarding schools plays a crucial role in realizing competitive Islamic boarding schools, adapting to current developments, and being open to renewal. This study aims to describe the planning, implementation, evaluation, and follow-up of collaborative development with educators to create competitive Islamic boarding schools. The study employed a qualitative approach with a multi-site case study design at Darunnajah Islamic Boarding School and Amanatullah Islamic Boarding School. Data were collected through observation, interviews, and documentation using purposive sampling techniques, and analyzed using triangulation. The research results show that, first, educator quality development planning tends to be conducted periodically, taking into account the complexity of the problems, the characteristics of human resources, and the needs of the development program. Second, the implementation pattern of educator quality development varies according to the governance and leadership style applied; the more participatory and adaptive the leadership, the greater the opportunity for integration between traditional values ​​and modern management practices. Third, educator quality evaluation generally includes aspects of institutional performance, the effectiveness of the learning process, educator self-reflection, and analysis of the institutional context. Fourth, follow-up to mutual development requires the implementation of sustainable mutual management principles realized through training programs, a tiered evaluation system, and consistent stakeholder involvement. This finding confirms that systematic and contextual development of educator quality is an important factor in building the competitiveness of Islamic boarding schools in the modern era.